A Role for Pre-mRNA-PROCESSING PROTEIN 40C in the Control of Growth, Development, and Stress Tolerance in Arabidopsis thaliana - Hernando, Carlos Esteban; García Hourquet, Mariano; de Leone, María José; Careno, Daniel; Iserte, Javier; Mora Garcia, Santiago; Yanovsky, Marcelo Javier (Frontiers in Plant Science, 2019)
Because of their sessile nature, plants have adopted varied strategies for growing and reproducing in an ever-changing environment. Control of mRNA levels and pre-mRNA alternative splicing are key regulatory layers that contribute to adjust and synchronize plant growth and development with environmental changes. Transcription and alternative splicing are thought to be tightly linked and coordinated, at least in part, through a network of transcriptional and splicing regulatory factors that interact with the carboxyl-terminal domain (CTD) of the largest subunit of RNA polymerase II. One of the proteins that has been shown to play such a role in yeast and mammals is pre-mRNA-PROCESSING PROTEIN 40 (PRP40, also known as CA150, or TCERG1). In plants, members of the PRP40 family have been identified and shown to interact with the CTD of RNA Pol II, but their biological functions remain unknown. Here we studied the role of AtPRP40C, in Arabidopsis thaliana growth, development and stress tolerance, as well as its impact on the global regulation of gene expression programs. We found that the prp40c knock-out mutants display a late-flowering phenotype under long day conditions, associated with minor alterations in red light signaling. An RNA-seq based transcriptome analysis revealed differentially expressed genes related to biotic stress responses, and also differentially expressed as well as differentially spliced genes associated with abiotic stress responses. Indeed, the characterization of stress responses in prp40c mutants revealed an increased sensitivity to salt stress, and an enhanced tolerance to Pseudomonas syringae pv. maculicola (Psm) infections. This constitutes the most thorough analysis of the transcriptome of a prp40 mutant in any organism, as well as the first characterization of the molecular and physiological roles of a member of the PRP40 protein family in plants. Our results suggest that PRP40C is an important factor linking the regulation of gene expression programs to the modulation of plant growth, development, and stress responses.